In vitro validation of chemo-transcriptomic fingerprints for the classification of the mode of action of antimalarial drugs - Birkholtz, Lyn-Marie (University of Pretoria, 2025)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.